Alcoholic Extract of Shilajit as Anti Protein Denaturation, Anti Blood Hemolysis, and Anti Microbial - Saba Hadi1, Sundus Hameed Ahmed1, Noor Talib1, Hassan Abdul Hussein1 and Isam Hussain T. Al-Karkhi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Shilajit is a natural material found mostly in the Himalayas (India), formed by the slow decomposition of certain plants by the action of microorganisms. It is an effective and extremely safe dietary supplement, and potentially able to prevent several diseases. Shilajit alcoholic extract was prepared by dissolving 10 grams of it in 200 mL of 95% ethanol. FTIR and other chemical procedures were used to detect the presence of Phenols, Alkaloids, Terpenoids, Tannins, Proteins Carbohydrates and, Steroids. Different concentrations of the extract were prepared and antimicrobial activity against several positive and negative gram stains, anti-protein denaturation and anti-blood cell hemolysis. Investigation results show that the nanoparticles were effective in inhibiting protein denaturation of albumin. Proteins denaturation refers the cause of inflammation, while the maximum inhibition of albumin was 87% observed at 300 ?g/ml of Shilajit alcohol extract compared with aspirin at the same concentration. The results of inhibiting hemolysis at 300?g/ml in comparing with standard drug Diclofenac sodium 300?g/ml resulted in good protection against the damaging effect of heat solution.